A two-dimensional limit discrete theorem for Mellin transforms of the Riemann zeta-function - Balinskaitė, Violeta (Lietuvos matematikos rinkinys, 2007)
In the paper two-dimensional limit theorem for the modified Mellin transform of the Riemann zeta-function is obtained.